PAREMIOLOGICAL TEXTS AND THE LINGUO-COGNITIVE ANALYSIS OF ZOONYMIC COMPONENTS - Yulduz Egamberdiyeva (Web of Journals Publishing, 2025)
This study examines the linguo-cognitive aspects of zoonymic components in paremiological texts, focusing on English and Uzbek proverbs. Proverbs, as an essential part of linguistic and cultural heritage, often contain animal references that reflect societal values, traditions, and cognitive perceptions. By analyzing selected proverbs, this paper explores the similarities and differences in how these two languages use zoonymic elements to convey wisdom and moral lessons. The study reveals that while some proverbs exhibit cross-cultural parallels, others reflect distinct cultural beliefs and environmental influences. This research highlights the role of language in shaping cognition and underscores the importance of understanding cultural perspectives through proverbial expressions.
Keywords: Paremiology, linguo-cognitive analysis, zoonymic components, proverbs, English, Uzbek, cultural cognition, metaphorical meaning.